(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the planning and organization of audit examinations in Uzbekistan, focusing on the institutional framework, methodological approaches, and challenges faced by audit firms operating under national legislation. Using a mixed-method empirical approach that combines regulatory analysis and expert interviews from leading audit firms, the paper identifies the core elements of effective audit planning, evaluates compliance with International Standards on Auditing (ISA), and proposes best practices for improving audit quality and efficiency. The findings suggest that while Uzbekistan has made significant progress in harmonizing its audit standards with international norms, gaps remain in strategic planning, risk assessment, and auditor independence.